2005
DOI: 10.1021/jp052662m
|View full text |Cite
|
Sign up to set email alerts
|

Unequal-Sphere Packing Model for Simulation of the Uniaxially Compressed Iodine Adlayer on Au(111)

Abstract: A simple unequal-sphere packing (USP) model, based on pure geometrical principles, was applied to study the centered-rectangular iodine c(p× 3)R30°adlayer on the Au(111) surface, well-known from surface X-ray structure (SXS), low energy electron diffraction (LEED), and scanning tunneling microscopy (STM) experiments. To reproduce the exact patterns observed in experiments, two selective conditionssminimum average adsorbate height and minimum adlayer roughnessswere imposed. As a result, a series of adlayer patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Examples are the low-temperature oxidation of CO and CH 4 and the water-gas shift reaction on gold nanoparticles [1][2][3] , oxygenpromoted dissociation of O 2 on Au{111} 4 , or chlorine-promoted selectivity in the oxidation of olefins and mercury 1,4,5 . The selectivity-enhancing effect of chlorine in particular and the general importance of halogens in electrochemical reactions have prompted a number of experimental and theoretical studies on halogen adsorption on the close packed {111} surfaces of the group 1B coinage metals Cu, Ag and Au [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are the low-temperature oxidation of CO and CH 4 and the water-gas shift reaction on gold nanoparticles [1][2][3] , oxygenpromoted dissociation of O 2 on Au{111} 4 , or chlorine-promoted selectivity in the oxidation of olefins and mercury 1,4,5 . The selectivity-enhancing effect of chlorine in particular and the general importance of halogens in electrochemical reactions have prompted a number of experimental and theoretical studies on halogen adsorption on the close packed {111} surfaces of the group 1B coinage metals Cu, Ag and Au [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 The selectivity-enhancing effect of chlorine in particular and the general importance of halogens in electrochemical reactions have prompted a number of experimental and theoretical studies on halogen adsorption on the close-packed {111} surfaces of the group 1B coinage metals Cu, Ag and Au. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Chemisorbed Cl layers display well-ordered phases, which make structure determinations possible with a number of experimental techniques. The experimental studies agree that Cl prefers fcc adsorption sites on Cu and Ag{111}.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the I-Au͑111͒ system, which possesses structures with long periodicity, could also be described by our unequal-sphere packing model. 21 Moreover, additional parameters could be used for identification of the most likely structures in the case of different adsorbate-substrate systems.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the iodine monolayer on the Au(111) surface can form a large variety of structures, from the commensurate (√3×√3) R 30°, to uniaxially compressed c( p ×√3) R 30° with variable p , to rotated hexagonal ones. The formation of these monolayers has been attributed to a competition between the complex atom−surface and atom−atom interactions . Nevertheless, the authors do not comment on this fact, and consequently, it is not clear in the paper which monolayer symmetry the iodine possesses (i.e., no surface structure analysis was performed).…”
mentioning
confidence: 99%
“…The formation of these monolayers has been attributed to a competition between the complex atom-surface and atom-atom interactions. 9 Nevertheless, the authors do not comment on this fact, and consequently, it is not clear in the paper which monolayer symmetry the iodine possesses (i.e., no surface structure analysis was performed). Finally, to obtain the hexagonal monolayer interaction energy, the authors multiply the pairwise interaction potential by 6 instead of the correct value of 3 (to avoid double counting for an atom i interacting with atom j).…”
mentioning
confidence: 99%